Understanding System. IO for .NET Core 3 : implementing internal and commercial tools - Villela, Roger (Apress, 2020)
Take full advantage of the .NET APIs in System. IO to achieve fundamental I/O operations and produce better quality software. Youll start with the basics of creating a .NET Core custom library for System. IO. You will learn the purpose and benefits of a custom cross-platform .NET Core library along with the implementation architecture of the custom library components. Moving forward, you will learn how to use the .NET APIs of System. IO for getting information about resources. Here, you will go through drives, directories, files, and much more in the .NET API. Youll discuss manipulation of resources and the environment, where you will learn how to build custom IO actions for resource manipulation followed by its properties and security. Next, you will learn special .NET API operations with System. IO with demonstrations on working with collection of resources, directories, files, and system information. Finally, you will go through the managed and unmanaged streams in the .NET API such as memory stream, file stream, and much more. After reading Understanding System. IO for .NET Core 3, you will be able to work with different features of .System. IO in .NET Core and implement its internal and commercial tools for different I/O scenarios. You will: Discover the inner workings of the System. IO BCL implementation on the .NET Core platform Work with System. IO mechanisms available through the .NET Core platform Write a custom library that encapsulates .NET APIs from System. IO Design and implement various tools in System. IO.